Debate: TAVI prosthesis selection for severe calcification. The self-expandable technology approach - Raquel del Valle Fernández (REC: Interventional Cardiology (English Ed.))
QUESTION: What are the implications of aortic valve calcification on the outcomes of transcatheter aortic valve implantation (TAVI)? ANSWER: By design, currently marketed TAVI prostheses require a certain degree of annular calcification to ensure proper fixation. In fact, treating non-calcified valves, such as in pure aortic regurgitation (a scenario for which TAVI has not been approved yet), is associated with a higher risk of malapposition, valve migration, and need for a second prosthesis.1 However, severe valve calcification also poses implantation challenges, as it may compromise the initial procedural success and long-term outcomes.2 Since the planning stage, the presence of severe calcification can hinder the accurate reconstruction of the aortic annular plane and the ability to obtain reliable measurements of its dimensions, thus introducing uncertainty into valve sizing. Procedurally, severe calcification is associated with a higher risk of immediate complications, such as annular rupture, aortic regurgitation (whether central or paravalvular), and conduction disturbances.3 Furthermore, severe calcification can impede valve crossing and limit the expansion of the prosthesis, which is why valvuloplasty prior to implantation is usually performed to ease valve crossing and allow for greater expansion and better apposition of the prosthesis to the annulus. This increases the number of maneuvers in the aortic...